2021
DOI: 10.3389/fpsyg.2021.760774
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Influence of Perceived Value on Social Attachment: Developing Country Perspective

Abstract: Perceived value has a positive impact on users’ social attachment in social media usage contexts and is a topic at the forefront of current research in consumer behavior. Although studies have begun to investigate the factors influencing social attachment, there is a lack of research on how perceived value affects social attachment. Therefore, this study uses privacy concern theory, to build a theoretical model with moderated and mediation roles, using Chinese Tik Tok users as data and survey sample, and apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 98 publications
2
18
0
2
Order By: Relevance
“…Fourth, this study proved the moderating effect of privacy concerns on the relationship between community identity and purchase intention in community group buying platform. The findings are consistent with the logical reasoning of Krafft et al (2017) , Yu (2018) , and Wang et al (2021) . It is hypothesized that the main reason for this may be the role of privacy concerns not only in terms of its direct impact, but also in terms of its effectiveness as an important moderating variable that can change the effect of other marketing factors on consumer behavioral responses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Fourth, this study proved the moderating effect of privacy concerns on the relationship between community identity and purchase intention in community group buying platform. The findings are consistent with the logical reasoning of Krafft et al (2017) , Yu (2018) , and Wang et al (2021) . It is hypothesized that the main reason for this may be the role of privacy concerns not only in terms of its direct impact, but also in terms of its effectiveness as an important moderating variable that can change the effect of other marketing factors on consumer behavioral responses.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that “in general, individuals psychologically perceive that they can share and communicate carefree on a secure virtual platform because they perceive high levels of perceived value and develop a sense of belonging in their continued use of that virtual platform. The impact of the privacy breach results is that users with higher privacy concerns are concerned about the collection, control, and use of personal information during the use of the medium, thus creating a perceived loss factor for using that community group purchase” ( Wang et al, 2021 ). This illustrates that if a user’s privacy concerns are more sensitive, then that user will expect enhanced privacy protection in their purchase intentions, resulting in lower purchase intentions.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…Social media has changed the way we interact, share, and communicate with others ( Vardeman-Winter and Place, 2015 ; Gao et al, 2021 ; Mujahid and Mubarik, 2021 ; Wang et al, 2021 ). Social media is “flexible enough to match our social capabilities and new ways of coordinating group action” ( Reitz, 2012 , p. 43).…”
Section: Introductionmentioning
confidence: 99%
“…Privacy concerns refer to users' perceptions and concerns about the collection, acquisition, monitoring, and use of personal information, reflecting the subjective feelings of individuals about the corresponding privacy situations (Son and Kim, 2008;Ou and Yuan, 2016;Wang et al, 2021). For a user in a virtual context, privacy concerns are an important prerequisite for making security decisions and an important antecedent variable for privacy behavior.…”
Section: Moderating Role Of Privacy Concernsmentioning
confidence: 99%